Continuous subcutaneous insulin infusion and flash glucose monitoring in diabetic hemiballism-hemichorea. (July 2020) - Qiang, Wei; Chen, Xia; Gao, Chuqi; Wang, Zhaoxu; Shang, Jin; Fu, Jiao; Guo, Hui
A 71-year-old man without previous history of diabetes was hospitalized after suffering polyuria for 1 month and involuntary movement of the left arm for 1 week. His random serum glucose was 42.05 mmol/l and his hemoglobin A1C was 14% (129 mmol/mol). His serum osmolarity was normal and his urine ketone was negative. Cerebral CT revealed hyperdensity in the right basal ganglia. The patient was diagnosed with diabetic hemiballism-hemichorea (HH). Intravenous insulin was given and later shifted to continuous subcutaneous insulin infusion. During the hospital stay, insulin titration was guided mainly by flash glucose monitoring (FGM). Finger-prick glucose was occasionally checked to verify the accuracy of the FGM. Rapid correction of severe hyperglycemia was achieved without hypoglycemia. HH resolved within 1 week after euglycemia was achieved. This case emphasized the importance of being alert for HH as the initial presentation of diabetes and neuroimaging negative diabetic HH. In addition, interstitial glucose-monitoring technologies including continuous glucose monitoring and FGM can facilitate inpatient intensive insulin therapy in diabetic HH by avoiding hypoglycemia.